2015
DOI: 10.1017/s1470542715000112
|View full text |Cite
|
Sign up to set email alerts
|

From Noun to Evaluative Adjective: Conversion or Debonding? DutchTopand Its Equivalents in German

Abstract: In this study, we address the ways in which nouns can give rise to new adjectives in Dutch and German. More specifically, the focus is on words with an evaluative meaning that can be used in a wide range of morphological and syntactic constructions in recent (and informal) language. For example, the German nounHammer‘hammer’ can be used inHammervorstellung‘very good performance’ orhammer film‘fantastic film’. In the literature, two distinct hypotheses can be found to account for the adjectival uses of such eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Such developments may not be that common in syntax, but they are very common in morphology. For example, a compound may be reinterpreted as an affixoid plus a host, after which the affixoid becomes productive and possibly turns into an affix or, through debonding, into an adjective (de Vries 1920-1922, Booij 2010, Van Goethem & Hüning 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Such developments may not be that common in syntax, but they are very common in morphology. For example, a compound may be reinterpreted as an affixoid plus a host, after which the affixoid becomes productive and possibly turns into an affix or, through debonding, into an adjective (de Vries 1920-1922, Booij 2010, Van Goethem & Hüning 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that debonding of intensifying prefixoids is a creative process of lexical innovation in Germanic languages, which may lead to the emergence of new intensifying adverbs or evaluative adjectives (cf. Battefeld et al 2018;Norde and Van Goethem 2014Van Goethem and De Smet 2014;Van Goethem and Hiligsmann 2014;Van Goethem and Hüning 2015). The present paper investigates to which extent the adjectival or adverbial uses of Dutch morphemes with "fake" semantics may be considered instances of debonding.…”
Section: Debondingmentioning
confidence: 99%
“…There are also a number of other examples in the literature of prefixoids debonding into adjectives (e.g. Norde 2009;Van Goethem and De Smet 2014;Van Goethem and Hüning 2015;Battefeld et al 2018).…”
Section: Debondingmentioning
confidence: 99%
“…It is a type of degrammaticalization; a controversial concept in contexts of language change, which has been claimed to be impossible (Haspelmath 1999). In the recent literature, though, several cases of debonding have been uncovered (Norde 2009: 186ff; Norde and Van Goethem 2014;Van Goethem and De Smet 2014;Van Goethem and Hiligsmann 2014;Van Goethem and Hüning 2015). Morphemes with the original meaning 'giant' (Dutch reuze, German Riesen) have been attested to have debonded: in these cases, reuze and Riesen grammaticalized into prefixoids which had the function of intensification or indication of large size, and later debonded into adjectives or adverbs with this same meaning (Van Goethem and Hiligsmann 2014;Norde and Van Goethem 2014).…”
Section: Introductionmentioning
confidence: 99%